Corporate Social Responsibility: A Business Strategy That Promotes Energy Environmental Transition and Combats Volatility in the Post-Pandemic World - Sofia Karagiannopoulou; Nikolaos Sariannidis; Konstantina Ragazou; Ioannis Passas; Alexandros Garefalakis (Energies, 2023)
Corporate social responsibility can assist in reducing the noise caused by pricing volatility and a lack of energy-efficient business solutions. The study’s objective is twofold: (i) to investigate the role of corporate social responsibility (CSR) in reducing volatility through the contribution of energy-efficient strategies; (ii) to identify research trends in the field that may indicate future research directions for the development of more dynamic strategies that will help in mitigating the impact of pricing volatility. A five-step bibliometric analysis was applied to address the research question. The findings were visualized by using bibliometric tools such as R Studio, Biblioshiny, and VOSViewer. Chinese academics have been revealed as pioneers in integrating CSR into corporate strategies to reduce volatility and support energy-efficient investments. Moreover, results indicate that financial institutions must embrace a new business model based on both CSR and environmental, social, and corporate governance (ESG) principles. Since very little is known about the interaction structure between CSR and ESG in the mitigation of price volatility, the purpose of this article is to bridge that knowledge gap. The pioneering character of this research—the construction of a business model based on the principles of CSR and ESG—contributes significantly to both the field’s knowledge and the practice of corporate sustainability management.